Notch activity mediates oestrogen-induced stromal cell invasion in endometriosis. Issue 4 (April 2018) - Li, Na; Zhang, Ling; Li, Qi; Du, Yu; Liu, Hengwei; Liu, Yi; Xiong, Wenqian
Abstract : Oestrogen has been reported to control the invasiveness of endometrial stromal cells in endometriosis. Notch signalling, a master regulator of cell invasion in tumours, is regulated by oestrogen in other diseases and hyperactivated in endometriotic stromal cells. Therefore, we hypothesized that an interaction between Notch signalling and oestrogen may exist in the regulation of endometrial stromal cell invasion, which is essential for the development of endometriosis. Western blot analysis of tissues showed that the expression levels of Notch components (JAG1 and NOTCH1) and Notch activity were markedly higher in ectopic endometria than in their eutopic and normal counterparts. Primary stromal cells obtained from normal endometria cultured with oestrogen presented significant increases in the expression of Notch components and Notch activity, the cytoplasmic and nuclear accumulation of NOTCH1 intracellular domain, the expression of matrix metallopeptidase 9 and vascular endothelial growth factor and cell invasiveness. Knockdown of NOTCH1 markedly alleviated oestrogen-induced matrix metallopeptidase 9 and vascular endothelial growth factor expression and cell invasion. ICI (an oestrogen receptor α antagonist) also blocked these oestrogenic effects. Oestrogen-responsive elements were found in the promoters of NOTCH1 and JAG1 . A luciferase reporter analysis revealed that oestrogen regulated the expression of Notch components via oestrogen receptor alpha, which is bound to oestrogen-responsive elements in the JAG1 and NOTCH1 promoters. Collectively, our findings indicate that oestrogen engages in crosstalk with Notch signalling to regulate cell invasion in endometriosis via the activation of oestrogen receptor alpha and the enhancement of Notch activity. Notch signalling blockade may therefore be a novel therapeutic target for endometriosis.